Faktor Penentu Stunting: Analisis Komparasi Masa Millenium Development Goals (MDGs) dan Sustainable Development Goals (SDGs) di Indonesia - Sri Widari; Nasri Bachtiar; Elvina Primayesa (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze, before and after the SDGs agenda in Indonesia, the determinants of stunting through household characteristics, mother characteristics and child characteristics. Stunting is a condition in which, due to direct and indirect causes, toddlers fail to thrive or are too short compared to children of their age and is a nutritional problem that is the government's focus.  Nationally, at the end of the Millennium Development Goals (MDGs) in 2015, the prevalence rate of stunting in Indonesia was 36.4 percent and 30.8 percent in 2018. This figure is still above the RPJMN target for 2019, namely 28% stunting and the WHO stipulation, namely 20% stunting prevalence in 2025 and 0% stunting prevalence in 2030 according to the SDGs target. Access to clean water, access to sanitation, access to health services, national health insurance, housing, underweight mothers, mothers with parental education, birth weight and premature births were the variables studied in this study. This research uses secondary data, processed with logistic regression, from Riskesdas in 2013 and 2018. Results showed that under-five birth weight, underweight mothers, shelter, access to sanitation, access to clean water and preterm birth had a significant (significant) association with the incidence of under-five stunting.